2021
DOI: 10.3390/cells10061339
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Astrocytes and Müller Glial Cells in the Retina for Survival and Regeneration of Retinal Ganglion Cells

Abstract: Astrocytes have been associated with the failure of axon regeneration in the central nervous system (CNS), as it undergoes reactive gliosis in response to damages to the CNS and functions as a chemical and physical barrier to axon regeneration. However, beneficial roles of astrocytes have been extensively studied in the spinal cord over the years, and a growing body of evidence now suggests that inducing astrocytes to become more growth-supportive can promote axon regeneration after spinal cord injury (SCI). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 93 publications
(185 reference statements)
0
25
0
Order By: Relevance
“…These factors include Bdnf, Cntf, and Igf1 (Kermer et al, 2000;Pernet and Polo, 2006;Yungher et al, 2015;Luo et al, 2016). Along this line, several studies have demonstrated that glial cells including Müller cells release growth factors, which can recue RGCs after axonal injury (Yoo et al, 2021). Thus, a question arises as to, albeit temporarily, why some RGCs are protected while others die when these factors are provided?…”
Section: Resistance and Susceptibility Of Retinal Ganglion Cell Subty...mentioning
confidence: 99%
“…These factors include Bdnf, Cntf, and Igf1 (Kermer et al, 2000;Pernet and Polo, 2006;Yungher et al, 2015;Luo et al, 2016). Along this line, several studies have demonstrated that glial cells including Müller cells release growth factors, which can recue RGCs after axonal injury (Yoo et al, 2021). Thus, a question arises as to, albeit temporarily, why some RGCs are protected while others die when these factors are provided?…”
Section: Resistance and Susceptibility Of Retinal Ganglion Cell Subty...mentioning
confidence: 99%
“…Astrocytes are an integral component of the neurovascular unit, regulating and maintaining the BRB [ 19 , 20 ]. Since we observe a retinal vascular phenotype with age in GC1 −/− mice, we investigated whether astrocytes were morphologically changed.…”
Section: Resultsmentioning
confidence: 99%
“…The migration of MG has been particularly characterized in response to the upregulation of growth factors such as EGF and VEGF [ 13 , 177 , 197 ]. Concentration gradients of VEGF have demonstrated to increase the chemotactic response of MG in vitro, which correlated to the increased concentration of VEGF in later stages of neovascular retinopathies in vitro (21484851, 24412518).…”
Section: Examining the Neuroprotective Response Of Mgmentioning
confidence: 99%
“…During initial, or short-term, gliosis, MG become reactive by undergoing hypertrophic changes in morphology, radial extension of cellular processes, and proliferation. These reactive behaviors are also accompanied by the upregulation of neurotrophic factors, cytokines and enhanced homeostatic regulation in MG to ensure neuronal survival and communication [ 13 ]. However, prolonged gliotic responses can produce excessive MG proliferation, which displaces adjacent neurons to disrupt synaptic networks, curtail transmission of photonic signaling, and impede retinal regeneration [ 14 ].…”
Section: Introductionmentioning
confidence: 99%